IC100 cyclotron based facility for production of nuclear filters as well as for scientific and applied research - Gikal, B.; Dmitriev, S.; Gulbekian, G.; Apel’, P.; Bashevoi, V.; Bogomolov, S.; Borisov, O.; Buzmakov, V.; Cherevatenko, A.; Efremov, A.; Ivanenko, I.; Ivanov, O.; et al. (Вопросы атомной науки и техники, 2008)
The complex based on the cyclotron IC100 of the Laboratory of Nuclear Reactions (JINR, Dubna, Russia) provides industrial fabrication of nuclear filters. During modernization the cyclotron was equipped with superconducting ECR-ion source and axial injection system. The specialized beam channel with two coordinates scanning system and equipment for irradiation of polymer films has been installed in the implantation part of the complex. High intensity heavy ion beams of Ne, Ar, Fe, Kr, Xe, I, W have been accelerated to 1 MeV/nucleon energy. The investigation of irradiated crystals features, irradiation of different polymer films have been provided. Also few thousands square meters of track films with holes in the wide range of densities have been produced. The cyclotron based complex is capable to solve different kinds of scientific and applied problems as well.